2015
DOI: 10.1155/2015/817313
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Conductive Hearing Loss and Unilateral Pulsatile Tinnitus Associated with a Dural Arteriovenous Fistula: Case Based Review and Analysis of Relationship between Intracranial Vascular Abnormalities and Inner Ear Fluids

Abstract: While pulsatile tinnitus (PT) and dural arteriovenous fistula (DAVF) are not rarely associated, the finding of a conductive hearing loss (CHL) in this clinical picture is unusual. Starting from a case of CHL and PT, diagnosed to be due to a DAVF, we analyzed relationship between intracranial vascular abnormalities and inner ear fluids. DAVF was treated with endovascular embolization. Following this, there was a dramatic recovery of PT and of CHL, confirming their cause-effect link with DAVF. We critically eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Interestingly, preoperative instrumental findings were consistent with left MD. A similar case was previously described by Cassandro et al, and our case represents the second description of this unusual combination in the literature [39]. We also review the current published literature reporting the association between DAVF and HL, and discuss the possible relationship between cerebrospinal fluid (CSF) pressure, vascular intracranial anomalies and inner ear fluid dynamics.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, preoperative instrumental findings were consistent with left MD. A similar case was previously described by Cassandro et al, and our case represents the second description of this unusual combination in the literature [39]. We also review the current published literature reporting the association between DAVF and HL, and discuss the possible relationship between cerebrospinal fluid (CSF) pressure, vascular intracranial anomalies and inner ear fluid dynamics.…”
Section: Introductionsupporting
confidence: 78%
“…Finally, Cassandro et al reported a complete receding of CHL and PT after endovascular embolization of a DAVF, similarly to our patient. Authors supposed a subclinical intracranial hypertension with abnormal venous drainage and, in turn, an excess of endolymphatic volume, resulting in an injury in the microcirculation of the stria vascularis [39,50]. Before providing a possible explanation for the symptoms and signs depicted in our patient, a brief recall on the relationships between intracranial vascular structures, CSF and inner ear fluids (perilymph and endolymph) should be presented.…”
Section: Discussionmentioning
confidence: 96%
“…This system addresses the internal noise made within oneself and prevents it from influencing external sound processing. Vascular murmurs, created by hemodynamic changes in blood flow, could lead to audible pulses, known as pulsatile tinnitus [10][11][12].…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%
“…1 Among the vascular etiologies, dural arteriovenous malformation and carotid-cavernous fistula are probably the most common causes. 2 Although rarely reported, intracranial venous sinus malformation may be directly related in patients with PT. These variations had been defined as diverticulum (aneurysm), stenosis, or both.…”
Section: Oy-stersmentioning
confidence: 99%